PENGALAMAN SISWA DALAM PASARAN MINUMAN KESEHATAN TRADISIONAL : ENTERPRENUERSHIP LESSON - Nisya Kartiko Dewi; Fatimah Khumaira (UHAMKA Press, 2022)
This research was conducted to find out how the utilization of business opportunities carried out by the entrepreneur even in the midst of the covid-19 pandemic. This article used qualitative research methods with a descriptive approach, observed by what’s going on around, and with the type of research used is the depiction of the phenomenon that was happening. The result of this research was this entrepreneur could saw the opportunities well, even in the pandemic period, then make a creation of entrepreneurial and marketing activities of a product that named